(untitled) (European Journal of Pure and Applied Mathematics, 2024)
We know that mathematical modeling is a serious agent to realize the dynamics of Breast Cancer development, spread, and educe new therapeutic approaches. The main target of this study is to use Simpson’s 1/3 rule as an efficient numerical scheme for integration to numerically treat the obtained fractional integral equations and reduce them to a set of algebraic equations. The fractional derivatives here are taken in the Caputo-Fabrizio (CF) sense. Particular assurance is located on elucidating the error analysis of the given scheme. The results acquired by implementing the Runge-Kutta method (RK4M) are compared to those obtained using the achieved results. The results explain that the implemented scheme offers a precise and effective agent for simulating this model. The primary benefit of the implemented method is that it relies on a small number of uncomplicated steps and does not have long-term effects.